2012
DOI: 10.1101/gad.184648.111
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Polycomb kinetics and mitotic chromatin binding distinguish stem cells from differentiated cells

Abstract: Epigenetic memory mediated by Polycomb group (PcG) proteins must be maintained during cell division, but must also be flexible to allow cell fate transitions. Here we quantify dynamic chromatin-binding properties of PH::GFP and PC::GFP in living Drosophila in two cell types that undergo defined differentiation and mitosis events. Quantitative fluorescence recovery after photobleaching (FRAP) analysis demonstrates that PcG binding has a higher plasticity in stem cells than in more determined cells and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 50 publications
(79 reference statements)
8
90
1
Order By: Relevance
“…Furthermore, experiments in Xenopus and in Dictyostelium discoideum indicate a requirement for methylation of the H3K4 residue itself in mediating epigenetic memory of transcriptional activity during mitosis: when the K4 residue of histone H3 is mutated to glutamate (Ng and Gurdon, 2008) or alanine (Muramoto et al, 2010), epigenetic memory of transcriptional activity across mitotic divisions is disrupted. PcG complexes also remain associated with mitotic chromosomes, although to a lesser extent than Trithorax, and they co-localize with H3K27me3 on metaphase chromosomes in mammalian cells (Vincenz and Kerppola, 2008;Follmer et al, 2012;Fonseca et al, 2012). Although current data provide good support for the heritability of both H3K4me3 and H3K27me3 individually during cell division, the stability of the poised chromatin state during mitotic metaphase has not been thoroughly examined yet.…”
Section: Proposed Role 3: Poising For Totipotency and Preparing For Rmentioning
confidence: 89%
“…Furthermore, experiments in Xenopus and in Dictyostelium discoideum indicate a requirement for methylation of the H3K4 residue itself in mediating epigenetic memory of transcriptional activity during mitosis: when the K4 residue of histone H3 is mutated to glutamate (Ng and Gurdon, 2008) or alanine (Muramoto et al, 2010), epigenetic memory of transcriptional activity across mitotic divisions is disrupted. PcG complexes also remain associated with mitotic chromosomes, although to a lesser extent than Trithorax, and they co-localize with H3K27me3 on metaphase chromosomes in mammalian cells (Vincenz and Kerppola, 2008;Follmer et al, 2012;Fonseca et al, 2012). Although current data provide good support for the heritability of both H3K4me3 and H3K27me3 individually during cell division, the stability of the poised chromatin state during mitotic metaphase has not been thoroughly examined yet.…”
Section: Proposed Role 3: Poising For Totipotency and Preparing For Rmentioning
confidence: 89%
“…Upon serum or anisomycin stimulation, MSK1-mediated phosphorylation leads to dissociation of the repressor HP1g (encoded by Cbx3) from HDAC1 gene promoter, resulting in transcriptional activation (Winter et al 2008b). Similarly, phosphorylation of S28 shows a negative impact on the Polycomb repressive complex association with mitotic chromosomes (Fonseca et al 2012) as well as with several gene promoters upon MAPK activation in interphase (Gehani et al 2010;Lau and Cheung 2011). The data presented here establish histone H3S28 phosphorylation as an important signal-induced chromatin modification that modulates the association of corepressor complexes with their target promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Using FRAP to measure transport rates FRAP experiments are usually analyzed by measuring fluorescence in the photobleached area, averaging data over several experiments, followed by fitting this average to a mathematical model--often just an exponential decay function--(for example, (Stevenson et al, 1995;Sprague and McNally, 2005;Fonseca et al, 2012;Huranová et al, 2010;Sekiya et al, 2009;Rino et al, 2008;Molenaar et al, 2004;Shav--Tal et al, 2004)). This approach is relatively simple and fast and might be sufficient for many purposes, but it does not take full advantage of a FRAP experiment.…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
“…Actual transport rates have been determined in intact cells, but only for over--expressed cargoes (Cardarelli et al, 2009(Cardarelli et al, , 2011Bizzarri et al, 2012), or under assumptions that are not valid for every system, such as infinite size cytosol (Gregor et al, 2007), or equilibrium between compartments (Pfeifer et al, 2010). Furthermore, with the exception of a few recent publications (Cardarelli et al, 2012;Pfeifer et al, 2010;Cardarelli et al, 2009Cardarelli et al, , 2011, all published data we found corresponds to population averages (see for example (Sprague and McNally, 2005;Fonseca et al, 2012;Huranová et al, 2010;Sekiya et al, 2009;Rino et al, 2008;Molenaar et al, 2004;Shav--Tal et al, 2004)) .…”
mentioning
confidence: 92%